2021
DOI: 10.3390/antibiotics10091077
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polymer-Coated Magnetic Nanoparticles with Antibacterial Properties: Synthesis and In Vitro Characterization

Abstract: Uniformly sized magnetite nanoparticles (Dn = 16 nm) were prepared by a thermal decomposition of Fe(III) oleate in octadec-1-ene and stabilized by oleic acid. The particles were coated with Sipomer PAM-200 containing both phosphate and methacrylic groups available for the attachment to the iron oxide and at the same time enabling (co)polymerization of 2-(dimethylamino)ethyl methacrylate and/or 2-tert-butylaminoethyl methacrylate at two molar ratios. The poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…The efficient hyperthermia induced by the intracellular MNPs upon exposure to an alternating magnetic field (AMF) significantly destroyed the bacteria/biofilms, suggesting the potential of using this simplified approach to destroy bacteria. In contrast to the reports on MNP functionalization to target the bacteria, 36,37 we demonstrate that the MNPs formed in situ can be directly employed to kill the bacteria/biofilms.…”
Section: Introductioncontrasting
confidence: 99%
“…The efficient hyperthermia induced by the intracellular MNPs upon exposure to an alternating magnetic field (AMF) significantly destroyed the bacteria/biofilms, suggesting the potential of using this simplified approach to destroy bacteria. In contrast to the reports on MNP functionalization to target the bacteria, 36,37 we demonstrate that the MNPs formed in situ can be directly employed to kill the bacteria/biofilms.…”
Section: Introductioncontrasting
confidence: 99%
“…This resulted from the presence of teichoic acids, which harbour fewer positively charged D-alanine residues than negatively charged phosphate groups [ 48 ]. Indeed, previous studies have shown that cationic NPs have a bactericidal effect given the interaction of the positive charges of NPs with the negatively charged bacterial cell walls, which ultimately triggers the lysis and death of bacteria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, cationic polymers i.e., PDMAEMA and poly [2-(dimethylamino) ethyl methacrylate-co-2-tert-butylaminoethyl methacrylate] [P(DMAEMA-TBAEMA)] were grafted on the surface of Sipomer PAM-200-coated Fe3O4 particles (MNP@S). The P(DMAEMA-TBAEMA)-coated magnetite particles possessed superior biocidal properties against both E. coli and S. aureus compared to those of P(DMAEMA)-coated one [44]. The effectiveness of coated MNP@S magnetite particles depended on the type of microorganism, dose of particles, solvent and their coating.…”
Section: Cationic Polymer Conjugates With Metallic Nanoparticlesmentioning
confidence: 99%